The First Firn Core From the Cordillera Darwin Icefield: Implications for Future Ice Core Research - Tetzner, Dieter R.; Thomas, Elizabeth R.; Allen, Claire S.; McCulloch, Robert D.; Perren, Bianca B.; McGuire, Amy; Segato, Delia; Temme, Franziska; Fürst, Johannes; Moser, Dorothea; Fernandoy, Francisco; Rada, Camilo; et al. (Journal of Geophysical Research: Atmospheres, 2025)
The Southern Hemisphere westerly winds (SHWWs) (45–65°S) are important regulators of the Southern Hemisphere climate. The scarcity of observational records at the core of the wind belt hinders our understanding of the environmental impact and long-term variability of the westerly winds. The Cordillera Darwin Icefield (CDI) (54–55°S) is favorably located to capture environmental changes at the current core of the SHWW belt. Here, we present chemical and microparticle records from the first firn core from the CDI. We evaluate regional climate reanalysis data using in situ automatic weather station observations and apply a downscaling approach to study regional-to-local environmental conditions at the firn core site. We use these records to assess the preservation of local-to-regional environmental information in the firn. Our CDI firn core records present minor post-depositional disruptions, preserving the original seasonality of locally sourced impurities. Local surface air temperature and melt estimations suggest the icefield has been progressively exposed to surface melt conditions, but not enough to produce significant melt at the firn core site. Air mass trajectories demonstrate air parcels are directly transported from local marine and terrestrial environments, establishing a route for the transport and deposition of chemical compounds and aerosols to the firn core site. These results highlight the potential of high elevation sites (>2,000 m a.s.l) in the CDI to hold valuable paleoenvironmental records directly from the core of the SHWW belt, records which are currently threatened by increasing surface air temperatures.
CRIS-Team Scopus Importer:2025-07-04
Keywords: aerosol transport; climate proxies; glacier melt; ice core; Patagonia; westerly winds